The Way to Hit 'Em Back!-poster (London)
1945 1939-1945 "The Way to Hit 'Em Back!-poster" [HFR0015], c. 1940 Ministry of Works poster c.1940 aimed at workers in the building industry. The cartoon by Daily Herald cartoonist, George Whitelaw, shows a family made homeless by bomb damage and the construction of a new war factory.